Assessing the Implementation of DRRM Programs Among Public Secondary Schools in the Second District of Northern Samar - Acebuche, Rowel C. (International Journal of Research in Interdisciplinary Studies, 2025)
This descriptive-correlational study evaluated how well public secondary schools in the second district of Northern Samar had implemented a school disaster risk reduction management system. The respondents were the SBM committee members and others in-charge in the school DRRM operations. A complete enumeration of the respondents was utilized and have employed a survey questionnaire as a primary tool in the data collection, which parts were adopted from the National Disaster Risk Reduction and Management (NDRRM) Plan, Hyogo Framework for Action. The public secondary schools in the second district of Northern Samar were situated in the coastal area, school risk maps were not displayed, and with small student population. Although funds allotment was observed, the school DRRM organizational structure was not in place. Furthermore, the public secondary schools in the second district of Northern Samar had implemented the DRRM program. Concluding that the profile of the schools and the status of implementation are significantly related. Lastly, the difference in the status of implementation of the DRRM Program based on topographic location was not significant. The findings suggest that despite the variation in topographical features and characteristics, public secondary schools in the second congressional district of Northern Samar are generally implementing DRRM programs to a similar extent across topographic locations.